2011
DOI: 10.1093/humupd/dmr030
|View full text |Cite
|
Sign up to set email alerts
|

The translational challenge in the development of new and effective therapies for endometriosis: a review of confidence from published preclinical efficacy studies

Abstract: Greater scrutiny of the preclinical efficacy models, end-points and experimental designs is needed if the desire of translating novel treatment approaches is to be realized for women with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 66 publications
0
38
0
1
Order By: Relevance
“…It is estimated that 51%-89% of published research cannot be reproduced in other laboratories. [18][19][20][21][22] This problem has been highlighted by a number of recent, high-profile commentaries from the pharmaceutical industry, 18,19,23 funding agencies, including the National Institutes of Health, 24,25 scientific journals, 26,27 veterinarians, 28 academics, and biostatisticians. [29][30][31][32][33][34][35][36] This is of particular importance when animal models are used to advance the development of clinical therapeutics.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%
See 3 more Smart Citations
“…It is estimated that 51%-89% of published research cannot be reproduced in other laboratories. [18][19][20][21][22] This problem has been highlighted by a number of recent, high-profile commentaries from the pharmaceutical industry, 18,19,23 funding agencies, including the National Institutes of Health, 24,25 scientific journals, 26,27 veterinarians, 28 academics, and biostatisticians. [29][30][31][32][33][34][35][36] This is of particular importance when animal models are used to advance the development of clinical therapeutics.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%
“…Systematic reviews have identified recurring methodologic weaknesses in preclinical studies. 18,19,23,24,34,35 Vulnerabilities include errors in statistical design (inadequate power, ad hoc, interim, and retrospective end point analysis), lack of randomization and blinding, and incomplete methods reporting. In addition, lack of transparency in data reporting allows investigators to selectively report positive results without including information about experiments that fail to support the desired effect.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that greater scrutiny of the preclinical efficacy of models, end points, and experimental designs are needed if the desire of translating novel treatment approaches is to be realized in women with endometriosis. 115 Recommendation. Appropriate animal and in vitro models for preclinical studies of endometriosis therapies should be agreed upon by the endometriosis research community.…”
Section: Animal and Other Preclinical Modelsmentioning
confidence: 99%